Communicative approach to foster speaking in an efl classroom at an intermediate level - Faicán, Janeth; Guncay, Rocío
This research paper is designed to propose communicative activities which will help to develop communication in an English classroom. In order to set up these communicative activities, we have to analyze certain aspects related to the principles of the Constructivism Theory and the Communicative Language Teaching. Based on the theoretical framework, we have suggested some communicative activities that will be applied to engage students in the learning process. The use of these activities along with a good class environment is essential for the process of learning English, due to the fact that it encompasses the use of communicative competence and authentic material. After we have set up the theoretical framework, we have been developed a practical booklet for an intermediate level. Thus, the Communicative Language Teaching -CLT- is the approach that supports our booklet. The main objective of each activity is to generate real communication in classes by using social contexts. With these activities, we believe that the learning process will be more dynamic and realistic. In this way, learner will be more motivated because these activities provide the tools to develop the communicative skill in English. If students can communicate with their classmates, the learning process will be more meaningful for them. In other words, through this booklet, students will develop the communicative competence which is very important in learning a new language. Through the proposed activities we want to emphasize the communicative competence because it facilitates an atmosphere where the students feel the need to communicate with their peers by using their real experiences.